2013
DOI: 10.1634/theoncologist.2013-0061
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Randomized Phase II Study to Evaluate the Safety and Efficacy of Acetyl-L-Carnitine in the Prevention of Sagopilone-Induced Peripheral Neuropathy

Abstract: Background. Peripheral neuropathy (PN) is a recognized side effect of microtubule‐targeting agents and the most clinically relevant toxicity observed with the epothilone sagopilone (SAG). Studies suggest that acetyl‐L‐carnitine (ALC) may prevent chemotherapy‐induced PN. We conducted a prospective, placebo (PBO)‐controlled, double‐blind, randomized trial to investigate the safety and efficacy of ALC for the prevention of SAG‐induced PN. Methods. Patients with ovarian cancer (OC) or castration‐resistant prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…A correlation between mitochondrial dysfunction and differentially expressed carnitine has been previously described in rats in the context of ifosfamide chemotherapy toxicity . Propionyl‐L‐carnitine and acetyl‐L‐carnitine have shown to be promising in the management of therapy‐induced peripheral neuropathy in PCa patients without affecting therapeutic efficacy, and androgen deprivation therapy has been shown to significantly decrease numerous carnitines, including octanoylcarnitine and decanoylcarnitine …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A correlation between mitochondrial dysfunction and differentially expressed carnitine has been previously described in rats in the context of ifosfamide chemotherapy toxicity . Propionyl‐L‐carnitine and acetyl‐L‐carnitine have shown to be promising in the management of therapy‐induced peripheral neuropathy in PCa patients without affecting therapeutic efficacy, and androgen deprivation therapy has been shown to significantly decrease numerous carnitines, including octanoylcarnitine and decanoylcarnitine …”
Section: Resultsmentioning
confidence: 99%
“…Differentially expressed plasma carnitine levels have been found in cancer patients, often ascribed to malnutrition . Clinically, L‐carnitine and its derivatives (acetyl‐L‐carnitine; propionyl‐L‐carnitine) are under study to combat wasting and chemotherapy‐induced peripheral neuropathy . Carnitine supplementation in several experimental models has been shown to slow down tumor growth .…”
mentioning
confidence: 99%
“…This is the first trial demonstrating that a nutritional supplement increased CIPN. A phase II European multicenter clinical trial failed to support the efficacy of ALC against the neurotoxicity induced by sagopilone, an analog of ixabepilone [47].…”
Section: Preventionmentioning
confidence: 99%
“…The therapeutic effect of ALC on DPN was supported by previous studies, in which ALC improved visual analog scale and other symptoms scores, as well as electrophysiological parameters 12,[19][20][21] . Additionally, ALC has also been studied to treat peripheral neuropathy induced by chemotherapy [23][24][25][26][27] or antiviral treatment [28][29][30] . Most of these trials were uncontrolled or placebo-controlled, and showed that ALC is efficacious and safe.…”
Section: Discussionmentioning
confidence: 99%